Primary Carcinoma in the Fallopian Tube: A Two Cases Report - Myriam García Tirada; Mario Joel Arroyo Díaz; Luis Enrique Pompa Montes de Oca; Ramón Portales Pérez; María Victoria López Soto (Medisur)
Primary carcinoma in the fallopian tube is a rare gynecological tumor. Its preoperative diagnosis is difficult because of its insidious and silent course. It is usually performed in the postoperative stage. This carcinoma is most frequently presented in post menopausal women. Its clinical and histological behavior is often similar to that of an ovarian cancer. In literature there are reports on the association between ovarian and endometrial cancer. Nevertheless, there are but few references to their association with fallopian tubes cancer. Two cases of primary cancer in the fallopian tubes, diagnosed in a 6 months period through post-surgical histology, that were treated in the Gynecology Service of the ¨Enrique Cabrera¨ General Teaching Hospital are presented. Their preoperative diagnoses were endometrial adenocarcinoma and ovarian cancer. It is relevant that one patient, with 44 years old, was diagnosed through endometrial biopsy performed to remove an intra uterine device. The result of that study was an endometrial adenocarcinoma that required surgery.